Qualitative exploration of intrinsic and extrinsic factors that influence acceptability of semisoft vaginal suppositories - Toral Zaveri; Kimberly A Powell; Kate M Guthrie; Alyssa J Bakke; Gregory R Ziegler; John E Hayes (BMC, 2018)
Abstract Background Vaginal microbicides are a promising means to prevent the transmission of HIV and other sexually transmitted infections, by empowering women to initiate use prophylactically when they perceive themselves to be at risk. However, in clinical trials, microbicides have shown mixed results, with the consistent finding that effectiveness varies substantially as a function of user adherence. Methods Based on the assumption that adherence is driven, at least in part, by product properties that influence acceptability, we used softgel technology to develop vaginal drug delivery systems in the intermediate texture space between solids and liquids to overcome potential shortcomings of current dosage forms. Here, we used focus groups and surveys to determine women's initial reactions (i.e., acceptance and willingness-to-try) for semisoft vaginal suppositories intended for HIV and STI prevention, with a specific focus on how perception of and preferences for vaginal suppositories may be influenced by product characteristics such as size, shape, and firmness. Results Via focus groups, we identified intrinsic and extrinsic factors relevant to acceptability of semisoft suppository prototypes. Willingness-to-try depended on factors like intended functionality, anticipated leakage, type of sex, recommended frequency of use, type of sexual partner, and perceived risk. When handled ex vivo, shape, size, and firmness of suppositories communicated information about ease of imagined insertion and handling, perceived effectiveness, anticipated awareness and comfort of the product in the body. These impressions were partly based on prior experience with vaginal products. Conclusions Sensory attributes appear to play a substantial role in women's preferences and willingness to try the semisoft suppositories. Using these methods during preclinical development should help efficiently optimize a final product that is both biologically efficacious and preferred by women, toward a goal of enhancing adherence and effectiveness.